Approach to Vaccine Hesitancy: A Case Report Conveying the CASE Approach - Şeyma Karatekin; Ebru Şenol; İrem Keskin (Çocuk Dergisi)
Vaccine hesitancy is a concept that has persisted from the time smallpox vaccine was first introduced to this day. When encountering vaccine-hesitant caregivers in clinical practice, it is important to approach vaccine hesitancy in accordance with evidence-based practices to effectively utilise the limited time available. Our case describes a 6-month and 20-day-old patient admitted to the paediatric ward with acute bronchiolitis and missed vaccinations. The patient’s mother revealed that she did not get the infant vaccinated after 2 months of age because she was influenced by people around her. A structured interview was conducted with the mother following the CASE method. After the interview, the mother decided to get her baby vaccinated. The infant received Hepatitis B, diphtheria, tetanus, acellular pertussis, inactivated polio, Haemophilus influenzae type b, and conjugated pneumococcal vaccines on the day of discharge. Subsequent clinic visits confirmed adherence to the vaccination schedule.